Utilization of palm oil sludge in poultry diet. 1. Dried palm oil sludge and its fermented product in broilerâs diet - Sinurat, A.P; Purwadaria, T; Ketaren, P.P; Zainuddin, D; Kompiang, I.P (Indonesian Journal of Animal and Veterinary Sciences, 2000)
Palm oil sludge a by product of palm oil industry is not commonly used in poultry feed due to some limiting factors such as low protein and amino acids content and high fiber content. These limiting factors were expected to be reduced by fermentation technology. Therefore an experiment was conducted to study the use of fermented (FLS) and non-fermented palm oil sludge (LS) for broiler chicken feed. Two hundred and ten day-old broiler chicks were used for this study. The birds were allocated into 35 cages with 6 birds in each cage. Each 5 group of birds were fed with one of 7 experimental diets. All diets were formulated with similar nutrient contents containing either LS or FLS at 3 different levels (5, 10 and 15%) and a control diet with no LS or FLS. The experimental diets were fed for 6 weeks and the performances were observed. Carcass yield, abdominal fat, weight of liver and gizzard were also measured at the end of the trial. The results showed that LS or FLS can be included in broilerâs diet, since the mortality, carcass yield, abdominal fat, liver and gizzard were not significantly affected. Best level inclusion of LS was 5%. Although inclusion of 10-15% LS did not affect growth and feed conversion significantly, the feed intake was significantly depressed. The best level inclusion of FLS was 10%, since higher level (15%) caused growth depression. Â  Key words: Palm oil sludge, fermentation, broilers